Household Waste Management System in Sumedang Dinas Lingkungan Hidup dan Kehutanan - Fepi Febianti (JRPA - Journal of Regional Public Administration, 2019)
This research is aimed analyzing the problems of household waste management system in Sumedang regency, obstacles in the household waste management system, and efforts to overcome the obstacles of the household waste management system in Sumedang regency at Dinas Lingkungan Hidup dan Kehutanan. The researcher used qualitative analysis based on descriptive method. The data were taken purposive sampling technique. Research informants by Waste Management and Gardening Division Head, Sanitation Services Section Head, Section Head of Waste Management Partnership and Development, Waste Management and Gardening Management Staff. The data were obtained through literature study and direct observation in the field. This study used Miles and Huberman’s theory with the steps: Reduction data, presentation data, Conclusion drawing/verification, and Triangulation. By using the methods above, it was found that the household waste management system is not good enought, because the soid waste management system is seen from the operationa technique to carry the transportation up to the finalstage in the landfill, the laws and reguations governing the clear waste management, inadequate activites in terms of institutional meeds of employees, the financing is still not enough and the participation of the people who are still less concerned about the waste. The obstacles in the household waste management include uneven service for all regions, lacked of staff, lack of facilities and infrastructure on waste management, the tools were broken, the cost of procurement of equipment is less, lack of maintenance costs, the people who throw garbage carelessly, dump location is very close to the residential.There were efforts to overcome these obstacles by expanding the service area, adding jobs, making good use of facilities and infrastructure, performing maintenance and quality tools, procurement of priority items, staff skills in repairing tools, repairing garbage dumps, maintaining cleanliness of dumps.